Advancing Discovery of Snail Mucins Function and Application - McDermott, Maxwell; Cerullo, Antonio R.; Parziale, James; Achrak, Eleonora; Sultana, Sharmin; Ferd, Jennifer; Samad, Safiyah; Deng, William; Braunschweig, Adam B.; Holford, Mandë (Frontiers in Bioengineering and Biotechnology, 2021)
Mucins are a highly glycosylated protein family that are secreted by animals for adhesion, hydration, lubrication, and other functions. Despite their ubiquity, animal mucins are largely uncharacterized. Snails produce mucin proteins in their mucous for a wide array of biological functions, including microbial protection, adhesion and lubrication. Recently, snail mucins have also become a lucrative source of innovation with wide ranging applications across chemistry, biology, biotechnology, and biomedicine. Specifically, snail mucuses have been applied as skin care products, wound healing agents, surgical glues, and to combat gastric ulcers. Recent advances in integrated omics (genomic, transcriptomic, proteomic, glycomic) technologies have improved the characterization of gastropod mucins, increasing the generation of novel biomaterials. This perspective describes the current research on secreted snail mucus, highlighting the potential of this biopolymer, and also outlines a research strategy to fulfill the unmet need of examining the hierarchical structures that lead to the enormous biological and chemical diversity of snail mucus genes.